Considerazioni etico-giuridiche a margine della Legge 10 febbraio 2020, n. 10 “Norme in materia di disposizione del proprio corpo e dei tessuti post mortem a fini di studio, di formazione e di ricerca scientifica” (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Law 10/2020 on the donation of one's own body and post-mortem tissue for study, training and scientific research, fills a gap in our legal system in this area. In this contribution, it is intended to highlight, in particular, how the progressive implementation of the law requires strategies for coordinating actions to ensure a truly free and informed choice and a gathering of consensus among citizens who, in turn, need to be adequately informed and facilitated about this possibility. Furthermore, it is intended to emphasize the importance of promoting an ethical-legal culture on the idea of “ethically sensitive” donation which, as in the case of the choice to donate one's own organs, needs to balance, on the level of public ethics, personal moral convictions and ethical standards that can be traced back to the principle of self-determination, solidarity and altruism.
Keywords: Body donation; self-determination; solidarity; Informed consent; rights and duties